A Web-Based Information System for Targeted Social Assistance Distribution in Rural Communities: Evidence from Bontoa Village, Indonesia - Ummiati Rahmah; Syahrul Syahrul; Muh. Amir; Bobur Sobirov (Yayasan Cendekiawan Digital Indonesia, 2025)
Social assistance distribution in Bontoa Village, Maros Regency, was previously handled through manual records, which reduced administrative efficiency, constrained transparency, and increased exposure to data manipulation. A web-based information system was designed and implemented to support targeted distribution for low-income households at the village level. System development followed the waterfall model, covering requirements analysis, system design, implementation, and testing. Empirical inputs were obtained from field observations, document analysis, and user involvement during evaluation. Functional validity was examined through black-box testing, while user acceptance was measured using a structured questionnaire administered to ten respondents representing village officials and community members. Descriptive quantitative analysis produced an average acceptance score of 87.2% (44/50), indicating strong perceived usability and relevance. The implemented system improved data accessibility, strengthened structured beneficiary management, and supported more efficient administrative workflows in distribution and reporting. These findings add empirical support for deploying web-based governance tools in rural social assistance settings where administrative capacity and information control remain limited.